Aspects of the Roman Public Law: Political Constitution of Monarchy and Republic (Revista da Faculdade de Direito, Universidade de São Paulo, 2005)
Brief outline of the Roman Public Law, namely of the so-called external history of Roman Law, with a delineation of the political constitution – that is to say, the organs of political representation as well as those of political rule and for the administration of justice in the civitas – during the monarchic and republican periods of Roman history.